2001
DOI: 10.1590/s1516-35982001000300004
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de uma pastagem de Coastcross-1 (Cynodon dactylon (L.) Pers) sob diferentes níveis de matéria seca residual

Abstract: RESUMO -O experimento foi realizado no período de agosto de 1997 a abril de 1998, com o objetivo de avaliar uma pastagem de Coastcross -1 (Cynodon dactylon (L.) Pers), em quatro níveis de resíduo de matéria seca (RMS: 1978(RMS: , 2130, 2545 e 3857 kg de MS/ha), com lotação contínua e carga animal variável. Foram determinadas a produção de matéria seca (PMS), a taxa de crescimento do pasto (TC), a acumulação líquida de MS (ALMS), a altura das plantas (AP), a porcentagem de solo descoberto (SD), a participação … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
11

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 7 publications
2
2
0
11
Order By: Relevance
“…Comparable forage accumulation rates were reported by Fagundes et al (1999), Carvalho et al (2000), and Bortolo et al (2001) in pastures maintained at different heights. The use of grazing exclusion cages is probably responsible for the non-detection of differences in FARs at different heights, as they can cause overestimation of FAR in lower canopies and underestimation of those kept higher (Bortolo et al 2001;Molan, 2004).…”
Section: Variablessupporting
confidence: 48%
See 1 more Smart Citation
“…Comparable forage accumulation rates were reported by Fagundes et al (1999), Carvalho et al (2000), and Bortolo et al (2001) in pastures maintained at different heights. The use of grazing exclusion cages is probably responsible for the non-detection of differences in FARs at different heights, as they can cause overestimation of FAR in lower canopies and underestimation of those kept higher (Bortolo et al 2001;Molan, 2004).…”
Section: Variablessupporting
confidence: 48%
“…Comparable forage accumulation rates were reported by Fagundes et al (1999), Carvalho et al (2000), and Bortolo et al (2001) in pastures maintained at different heights. The use of grazing exclusion cages is probably responsible for the non-detection of differences in FARs at different heights, as they can cause overestimation of FAR in lower canopies and underestimation of those kept higher (Bortolo et al 2001;Molan, 2004). However, Grant et al (1983) and Bircham & Hodgson (1983) reported that the tiller size/density compensation in plant communities subjected to defoliation can make large variations between defoliation regimes result in small differences in the total amount of leaves produced per unit area.…”
Section: Variablessupporting
confidence: 48%
“…Na fração material morto, também não houve diferença entre os sistemas, sendo, em média, de 6,7 e 14,4%, no pré e pós-pastejo, respectivamente, este aumento se dá em função do pisoteio e da seleção dos animais por forragem verde. Os maiores valores foram observados no período estival, devido ao aumento de material senescente da Coastcross-1, notadamente no outono (BORTOLO et al, 2001), e ao efeito cumulativo do pisoteio.…”
Section: Resultsunclassified
“…Já para os valores de pós-pastejo, as médias foram de 0,78; 0,44; 0,32 e 0,38, respectivamente. Para todos os sistemas, houve uma tendência de diminuição dos valores obtidos no decorrer dos pastejos, devido à maturação das plantas (BORTOLO et al, 2001). - CV (%) 10,9 11,7 9,2 10,0 Médias seguidas por letras distintas, minúsculas na linha e maiúsculas na coluna, diferem entre si (P<0,05) pelo teste de Tukey.…”
Section: Resultsunclassified
“…Fact that proves that even at grazing being lowered to a lower height (30% of input height), it can provide the same production over its cycle, most likely by good soil fertility and nitrogen fertilization, which was performed after the first three collections, period that run-up water restriction. Bortolo et al (2001) neither found difference in total forage production evaluating coastcross pasture under eight different residual levels. A similar result was found by Marcelino et al (2006), which reported no difference in marandu grass yield under two grazing intensities (10 and 20cm).…”
Section: Rocha Et Al (2007) Evaluating Black Oat Andmentioning
confidence: 71%